Analysis of Toddler Health Service Access and Stunting Incidence in East Bolaang Mongondow Regency - Enternity Jusi Katuche; Alexander Sam Leonard Bolang; Victor Paskah Kalawat Lengkong (LPPM Universitas Harapan Bangsa, 2024)
Stunting is a chronic nutritional issue in children, characterized by shorter stature than their peers, affecting their growth and development. This study aims to analyze the relationship between access to healthcare services and the incidence of stunting among toddlers in East Bolaang Mongondow Regency. The research employs a mixed-methods approach, using a cross-sectional observational analytical design for quantitative aspects and qualitative analysis for supporting factors. The study sample includes 976 toddlers, with secondary data from the 2022 Indonesian Nutrition Status Survey (SSGI). Variables examined include access to healthcare facilities, Maternal and Child Health (MCH) book ownership, and immunization services. Data analysis revealed significant relationships between visits to healthcare facilities (p=0.000) and immunization services (p=0.000) with stunting incidence, although the correlations were weak (c=0.127; c=0.114). However, no significant relationship was found between ownership of MCH books and stunting. Immunization services emerged as the most influential factor in stunting incidence. Significant barriers included distance, transportation costs, and parents' lack of knowledge and awareness. Recommended interventions include intensive health promotion programs to raise community awareness about the importance of immunization and regular healthcare visits, as well as expanding access to immunization by increasing schedules at health centres and integrated service posts (posyandu) located closer to communities.